2016
DOI: 10.18632/oncotarget.13413
|View full text |Cite
|
Sign up to set email alerts
|

Re-purposing of curcumin as an anti-metastatic agent for the treatment of epithelial ovarian cancer: in vitro model using cancer stem cell enriched ovarian cancer spheroids

Abstract: Malignant epithelial ovarian cancer (EOC) spheroids high frequently are detected in the malignant ascites of the patients with the extensive peritoneal metastasis of ovarian cancer, which represent a significant obstacle to efficacious treatment. Clinical data also suggested that EOC spheroids play a putative role in the development of chemoresistance. Since standard surgery and conventional chemotherapy is the only available treatment, there is an urgent need to identify a more effective therapeutic strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…It is further shown that curcumin causes loss of proliferation of oral cancer and CSCs. Our findings are consistent with previous studies on breast ( 22 ), colon ( 9 ), cervical ( 11 ), and ovarian cancer ( 23 ). Curcumin treatment inhibited cell viability more effectively in HPV+ve and HPV–ve parental and NSP than that of CSCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is further shown that curcumin causes loss of proliferation of oral cancer and CSCs. Our findings are consistent with previous studies on breast ( 22 ), colon ( 9 ), cervical ( 11 ), and ovarian cancer ( 23 ). Curcumin treatment inhibited cell viability more effectively in HPV+ve and HPV–ve parental and NSP than that of CSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Less cytotoxic effect on CSCs could be attributed to limited penetration or inadequate availability of curcumin to SP cells. Similar results were also observed in earlier studies ( 23 , 24 ). However, inhibition of proliferation was found to be highly pronounced in HPV+ve CSCs than that of HPV–ve CSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Curcumin could induce apoptosis in cancer cells [19] , [20] , [21] , [22] , [23] , [24] as well as inhibit VEGF and osteopontin-induced angiogenesis [25] , [26] . Furthermore, curcumin inhibits H 2 O 2 -induced invasion of pancreatic cancer [27] and blocks invasion of ovarian cancer spheroids into the mesothelial monolayers [28] . In addition, many groups have reported that curcumin enhances TRAIL-, 5-fluorouracil-, gemcitabine- and irradiation-induced cell death [29] , [30] , [31] , [32] , [33] , [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial ovarian carcinoma (OC) is the most common type of OC, accounting for 90% of ovarian tumors. Symptoms of OC are detected late resulting in diagnosis at stages III and IV [ 10 , 11 ]. In addition, the highly metastatic nature of OC results in low patient survival with a mortality of approximately 60% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%